An integrative review: maternal engagement in the neonatal intensive care unit and health outcomes for U.S.-born preterm infants and their parents - Susanne Klawetter; Jennifer C. Greenfield; Stephanie Rachel Speer; Kyria Brown; Sunah S. Hwang (AIMS Press, 2019)
Hospitals and perinatal organizations recognize the importance of family engagement in the neonatal intensive care unit (NICU). The Agency for Healthcare Research and Quality (AHRQ) defines family engagement as "A set of behaviors by patients, family members, and health professionals and a set of organizational policies and procedures that foster both the inclusion of patients and family members as active members of the health care team and collaborative partnerships with providers and provider organizations." In-unit barriers and facilitators to enhance family engagement are well studied; however, less is known specifically about maternal engagement's influence in the NICU on the health of infants and mothers, particularly within U.S. social and healthcare contexts. In this integrative review, we examine the relationship between maternal engagement in the NICU and preterm infant and maternal health outcomes within the U.S. Results from the 33 articles that met inclusion criteria indicate that maternal engagement in the NICU is associated with infant outcomes, maternal health-behavior outcomes, maternal mental health outcomes, maternal-child bonding outcomes, and breastfeeding outcomes. Skin-to-skin holding is the most studied maternal engagement activity in the U.S. preterm NICU population. Further research is needed to understand what types of engagement are most salient, how they should be measured, and which immediate outcomes are the best predictors of long-term health and well-being.